2018
DOI: 10.1128/jvi.01270-18
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T Cells, CD8 T Cells, and Monocytes Coordinate To Prevent Rift Valley Fever Virus Encephalitis

Abstract: Rift Valley fever virus (RVFV) is an arbovirus that causes disease in livestock and humans in Africa and the Middle East. While human disease is typically mild and self-limiting, some individuals develop severe manifestations, such as hepatitis, hemorrhagic fever, or encephalitis. Encephalitis occurs 2 to 3 weeks after acute illness; therefore, we hypothesized that it was a result of an inadequate adaptive immunity. To test this hypothesis in vivo, we used an attenuated virus (DelNSsRVFV) that does not typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…A series of studies performed in the mouse model revealed that monocytes, CD4 T cells, and CD8 T cells played a role in preventing RVFV-mediated encephalitis in the context of an active innate immune response, and that B cells contributed to viral clearance. 12,13 These key findings suggested that T cells may be involved in modulating RVFV disease, and are further supported by the discovery that HIV- positive patients infected with RVFV had increased case fatality rates and increased occurrence of CNS manifestations of disease. 14,15 The role of antibodies in disease protection prior to or shortly following exposure to a pathogen is well-established in infectious disease.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A series of studies performed in the mouse model revealed that monocytes, CD4 T cells, and CD8 T cells played a role in preventing RVFV-mediated encephalitis in the context of an active innate immune response, and that B cells contributed to viral clearance. 12,13 These key findings suggested that T cells may be involved in modulating RVFV disease, and are further supported by the discovery that HIV- positive patients infected with RVFV had increased case fatality rates and increased occurrence of CNS manifestations of disease. 14,15 The role of antibodies in disease protection prior to or shortly following exposure to a pathogen is well-established in infectious disease.…”
Section: Discussionmentioning
confidence: 79%
“…Recent data obtained in the mouse model suggested that the T cellmediated immune response, not just the antibody response, could be important in protecting animals (and by extension, humans) from disease. 12,13 Additionally, two reports assessed HIV-positive patients who acquired RVFV infection; these patients exhibited increased frequency of central nervous system (CNS) symptoms and a significantly higher case fatality rate than HIV-negative patients, 14,15 suggesting the importance of CD4 T cells in preventing CNS manifestations and decreasing the severity of RVFV disease. Given these findings, it was of interest to quantitate and characterize T cell-mediated immune responses in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adaptive immunity could also modulate disease in humans since HIV-1-positive individuals are more likely to suffer from encephalitis (6,38). These phenomena are partially represented in murine models; mice with various forms of altered innate and/or adaptive immunity develop late-onset encephalitis following infection with a highly attenuated version of RVFV that has a deletion of the nonstructural small (NSs) protein, the major virulence factor (39,40). Additionally, BALB/c mice sometimes develop late-onset encephalitis (13) although the mechanisms that modulate this phenotype are unknown.…”
Section: Discussionmentioning
confidence: 99%
“… Inhibition of type I IFN responses [ 167 , 168 , 169 ] Unclear . Reduced NK cell numbers in hyper-susceptible mice [ 170 ], but depletion does not increase susceptibility in resistant mice [ 171 ] Unlikely . NK cell depletion does not improve disease outcome in mice [ 171 ] Rabies Rhabdoviridae Bats, dogs, raccoons Bites Extremely rare Fever, nausea, vomiting.…”
Section: Prefacementioning
confidence: 99%